Plant regeneration in Piper longum L. (Piperaceae) through direct and indirect adventitious shoot development - LAWRENCE, G M NAIR, V SARASAN, ELIZABETH THOMAS, BEENA (Journal of Spices and Aromatic Crops, 1993)
Methods for large scale multiplication of Piper longum are reported. Shoot tips cultured on Murashige & Skoog’s medium supplemented with 0.5 mgl-1 benzyl adenine or kinetin in combination with 0.5 mgl-1 I-naphthalene acetic acid developed multiple shoots at very low frequency. Multiple shoots originated in large numbers, only from nodes of vertically planted explants, while shoots dnveloped de novo from all over the surface, when planted horizontally in the same medium containing 2·5 mgl-1 benzyl adenine. Leaf segments also developed adventitious buds in large numbers in Murashige & Skoog’s medium containing 3 mgl-1 benzyl adenine, I mgl-1 kinetin and 10% (v/v) coconut water. Callus induced from leaf and stem explants in Murashige & Skoog’s medium with 1-2 mgl-1 2, 4 dichlorophenoxy acetic acid in combination with Imgl-1 benzyl adenine developed shoot buds when transferred to medium containing 3 mgl-1 benzyl adenine. All the shoots were rooted in Murashige & Skoog’s basal medium. The isolated plantlets, hardened in vermiculite were transferred to pots containing garden soil and sand.